Effects of induction with novel agents versus conventional chemotherapy on mobilization and autologous stem cell transplant outcomes in multiple myeloma - Benson, Don M (2010)
MM is the top indication for high-dose chemotherapy (HDC) with autologous stem cell transplantation (SCT), a strategy which improves progression-free survival and potentially overall survival. Novel induction regimens incorporating the immunomodulatory (IMID) agents thalidomide and lenalidomide, and the proteosome inhibitor bortezomib improve response rates and survival for newly diagnosed patients. Recent data temper enthusiasm for these treatments by illustrating difficulty in some circumstances with mobilizing CD34(+) hematopoietic stem cells for subsequent HDC/SCT. We compare conventional induction regimens with novel-agent based induction strategies and the associated effects on stem cell mobilization and HDC/SCT outcome in 397 patients. Although patients exposed to novel agent inductions collected generally fewer CD34(+) cells than patients induced with chemotherapy, these differences did not translate into adverse consequences with subsequent HDC/SCT. We show that an improvement in overall survival following HDC/SCT may be related to induction therapy with novel agents as opposed to chemotherapy. Our data extrapolate on prior work and expand on ongoing controversies about optimal induction regimens for MM patients planned for subsequent HDC/SCT and optimal sequencing of therapies.